PELATIHAN PENYUSUNAN RENCANA PELAKSANAAN PEMBELAJARAN (RPP) BERBASIS KURIKULUM 2013 DI SMP MUHAMMADIYAH 1 PURWOKERTO - Dodi Siraj Muamar Zain; Titi Wahyukti; Endang Kusrini (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2018)
This community service aimed at training teachers of SMP Muhammadiyah 1 Purwokerto in developing lesson plans which are based on the curriculum 2013. During the training, teachers were not only presented the structure of lesson plans yet they got explanation about teaching practices based on the curriculum 2013. They involved the concept of scientific approach and students-centered learning. It is expected that this activity can assist teachers in developing lesson plans and constructing teaching activities based on the applied curriculum.